Callaloo Nation : Metaphors of Race and Religious Identity among South Asians in Trinidad - Khan, Aisha, 1955- (Book collections on Project MUSE., 2004)
Analyzes the relationship between conceptions of racial and ethnic identity and the ways social stratification and inequality are reproduced and experienced in the Republic of Trinidad and Tobago.